Economic analysis of the efficiency of hospitals (Economic and Political Thought, 2015)
The article presents the basics of economic analysis of the efficiency ofhospitals. In the first part, the concept of efficiency is defined on the basisof Pareto’s legacy. Because efficiency can be measured in several ways, thearticle presents the approach to the economic efficiency of production, whichis the product of technical and allocative efficiency, from the perspectiveof costs, revenues and profits. The second section describes the two mainmethods for estimating efficiency, namely the method of DEA drawn fromlinear programming and the econometric method of the SFA representingstochastic and parametric approach. Attention is focused on the problemsof determining the efficiency of hospitals and the healthcare system in thefollowing four points. The first issue is whether hospitals achieve economicefficiency understood as a product of technical and allocative efficiency.The second issue, although connected with allocative efficiency, is treatedas a separate one because of its significance. It concerns checking whetherhospitals are overcapitalized. The third issue refers to the impact of the costsincurred by hospitals on the degree of their specialization. The last issueconcerns the impact of the number of hospitals on costs incurred by hospitalsand the healthcare system.